Linking the Essential Core Competencies to Pediatric Content in an Entry-Level Physical Therapy Education Curriculum: A Case Report. Issue 4 (December 2017) - Cech, Donna; Krzak, Joseph J.; Anderson, Deborah K.
Abstract : Background and Purpose: In 2012, the Section on Pediatrics (SoP) established five Essential Core Competencies in Entry-Level Pediatric Physical Therapy Education representing the expected pediatric knowledge base, skills, and abilities of all graduating physical therapist (PT) students. To facilitate the integration of the Core Competencies within curricula and to achieve intended academic objectives, educators need tools to connect or "link" specific didactic content to each of the five Core Competencies and their associated subcriteria. The purpose of the current case report was to introduce a novel systematic approach using linking rules to demonstrate comprehensive inclusion of Essential Core Competencies within professional (entry-level) PT education programs. Case Description: Course descriptions and objectives within the curriculum of an accredited entry-level physical therapy professional program were reviewed for pediatric content. Two investigators independently assigned pediatric curriculum content to the 5 Essential Core Competencies using 10 linking rules. A third investigator was used to establish a consensus during the linking process. Frequencies and percentages representing the inclusion of each of the competencies and their associated subcriteria were calculated. Percent agreement and Cohen's kappa (κ) between the two independent investigators were calculated to evaluate the interrater reliability of the linking process. Outcomes: One hundred sixty-five (17%) of the 976 course objectives within the entry-level physical therapy professional program contained pediatric content. All 5 of the Essential Core Competencies were represented at varying degrees: human development (17%), age-appropriate patient/client management (51%), family-centered care for all patient/client and family interactions (6%), health promotion and safety (12%), and legislation, policy, and systems (7%). The remaining objectives (7%) were considered either General Pediatric Content or Not Covered by the Core Competencies, or Not Definable. The linking process had substantial interrater reliability (κ = 0.76; standard error = 0.09; 95% confidence interval = 0.60–0.93) between the two independent investigators. Discussion and Conclusion: A systematic approach to linking pediatric curriculum content to the Essential Core Competencies was introduced and applied using an integrated professional (entry-level) physical therapy education program. Such reliable systematic processes support best educational practice by confirming that all relevant pediatric content is preserved throughout an integrated physical therapy curriculum and ensures that PT students are provided with the essential knowledge base, skills, and abilities needed to successfully work with children. Future research should apply the linking strategies to nonintegrated physical therapy curricula, programs in other geographic regions, and content outside of pediatrics. Abstract : Supplemental Digital Content is Available in the Text.